Localized osseous involvement in cryptococcosis: Case report and review of the literature - Ong, T.H.; Prathap, K. (Wiley, 1970)
Bony lesions caused by Cryptococcus neoformans in the absence of a disseminated disease are uncommon. A case of a solitary osseous lesion is recorded, and a review of skeletal involvement in cryptococcosis is discussed. Copyright © 1970, Wiley Blackwell. All rights reserved